The Ballod kurgan. Research methods and the reconstruction of the funeral rite (Studia Archaeologica, 2023)
The Ballod Kurgan is the largest tomb among the Xiongnu burials located in the north of Mongolia, in the Noin-Ula Mountains. The study of the famous archaeological site was started with the excavations of the object by A.Ya. Ballod in 1913. Ten years later, in 1924, members of the Mongol-Tibetan expedition led by P.K. Kozlov re-examined the stratigraphy of the kurgan and completed the excavations of the burial chamber. Until the 2010s, the materials of that tomb were practically not taken into account in archaeological research, since information about it was scarce and scattered. The reason was the division of archaeological collections and archival documents among different scientific institutions in the first third of the twentieth century.A comprehensive analysis of all identified archaeological, written and visual sources made it possible to correct ideas about the stratigraphy of the grave pit, to restore the system of complex ceilings of the wooden burial chamber, to determine the features of its internal structure, and to reconstruct the arrangement of objects in the ‘corridors’ and the inner chamber of the burial structure. The peculiarities of the funeral rite and the set of accompanying inventory make it possible to consider this burial as the main kurgan in the Tzurumte Pad’ and, in general, in the Noin-Ula archaeological complex.Баллодын булш Оршуулгын зан үйлийн нэхэн сэргээлт түүний судалгааны арга зүйТовчлол. Баллодын хэмээн нэрлэгдсэн булш нь Монголын хойд хэсэгт орших Ноён уулын хүннүгийн үеийн булшнуудаас хамгийн том нь юм. 1913 онд А.Я.Баллод уг булшийг малтсанаар энэхүү гайхамшигт дурсгалт газрын судалгаа эхэлсэн. Үүнээс арав гаруй жилийн дараа 1924 онд П.К.Козловын удирдсан Монгол-Түвэдийн экспедицийн судлаачид энэхүү булшийг бүрэн хэмжээгээр нь малтан судалж, бунхныг малтаж дуусгасан байна. 2010 оныг хүртэл энэхүү булшны олдвор, эх хэрэглэгдэхүүн археологийн судалгааны эргэлтэд, түүний тухай мэдээлэл бүрэн бус, харилцан адилгүй байсантай холбоотой юм. Энэ нь XX зууны эхний гурван арваныг дуустал хугацаанд археологийн олдвор хийгээд архивын тэмдэглэлүүд нь хэд хэдэн эрдэм шинжилгээний байгууллагуудад байрлаж байжээ.Археологийн олдворууд дэлгэрэнгүй тэмдэглэлүүдийг нэгтгэн судалсны дунд булшны ерөнхий зохион байгуулалт, онцгой содон хийц бүхий модон бунхны бүтэц, дотоод засал, бунханд хүрэх зам зэргийг сэргээн тодруулах боломжтой болсон. Оршуулгын зан үйл, булшинд дагалдуулсан эд өлгийн зүйлсэд тулгуурлан Ноён уулын Зурамтын аманд орших хүннүгийн язгууртны хамгийн гол дурсгал энэ булш байжээ хэмээн дүгнэж байна.Түлхүүр үг: Хүннү, Ноён уул, Баллодын булш, Оршуулгын зан үйл, Архивын баримт